Analisis Puisi “Penerimaan” Karya Chairil Anwar Dengan Pendekatan Struktural (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Poetry is one of the literary genres that expresses feelings. Poetry is a poet's interpretation of life. The interpretation reflects the poet's view of the surrounding reality. Therefore poetry is a form of outpouring of thoughts and feelings poet to the reality of life. The reason the author analyzed the poem by Chairil Anwar entitled "Acceptance" is to understand and also capture the meaning of the poem "Acceptance" by Chairil Anwar. In analyzing this poem, the author uses a structural approach. To analyze poetry using a structural approach requires a basic understanding of the structure or elements that make up the poem itself.